Wall avoiding balbot - Sia, Lih Yin (2010)
In this project, a wall avoiding Balbot is presented. The purpose of this project is to develop a path control algorithm in Balbot so that it will avoid wall when at certain range of distance. The Balbot performs the task based on the sensorial information given by two IR sensors. Atmel Atmega32 microcontroller as its brain, Atmega32 receives input from IR distance sensor and then a control signal is generated to control the mobile robot’s position. The Balbot is drive through to the wall, the sensor will detect the distance and Balbot will turn to the right side to avoid the wall.